(Brian Thomas hw2 rhea)
 
m
 
(4 intermediate revisions by the same user not shown)
Line 1: Line 1:
 
==Part A==
 
==Part A==
 
We are given the following:
 
We are given the following:
<math>X_k[n]=\delta[n-k] \rightarrow \text{ system } \rightarrow Y_k[n]=(k+1)2 \delta[n-(k+1)] \ (k \in \mathbb{Z}, k \geq 0)</math>
+
<math>X_k[n]=\delta[n-k] \rightarrow \text{ system } \rightarrow Y_k[n]=(k+1)^2 \delta[n-(k+1)] \ (k \in \mathbb{Z}, k \geq 0)</math>
  
 
Translate this into math:  (See [[HW2-D_Brian_Thomas_ECE301Fall2008mboutin#Definition_of_Time_Invariance|this]] for symbology.)
 
Translate this into math:  (See [[HW2-D_Brian_Thomas_ECE301Fall2008mboutin#Definition_of_Time_Invariance|this]] for symbology.)
  
Let <math>x=\delta[n]</math>.  We are given that the system f works in the following way:
+
We are given some signal <math>x_k=\delta[n-k]</math> and a system <math>f(x_k) = f(\delta[n-k])) = (k+1)^2 \delta[n-(k+1)]</math>.  To show f is time-invariant, we must prove the following statement:
  
<math>f(S_k(x)) = f(S_k(\delta[n])) = f(\delta[n-k]) = (k+1)^2 \delta[n-(k+1)]</math>
+
<math>S_{k_0}(f(x_k)) = f(S_{k_0}(x_k)) \forall k_0 \text{ and }\forall k \in\mathbb{N}\cup{0}</math>
  
To show whether f is time invariant or time variant, we must examine the following:
+
<math>f(S_{k_0}(x_k)) = f(S_{k_0}(\delta[n-k])) = f(\delta[n-(k+k_0)]) = (k+k_0+1)^2 \delta[n-(k+k_0+1)]</math>
  
<math>S_k(f(x)) = S_k(f(\delta[n])) = S_k(\delta[n-1]) = \delta[n-(k+1)]</math>
+
<math>S_{k_0}(f(x_k)) = S_{k_0}(f(\delta[n-k])) = S_{k_0}((k+1)^2 \delta[n-(k+1)]) = (k+1)^2 \delta[n-(k+k_0+1)]</math>
  
Since <math>\exists (k \geq 0) \in \mathbb{Z} \ s.t. \ S_k(f(x)) \neq f(S_k(x))</math>  (e.g., if k=1), f (ie, the "system") is '''time variant'''.
+
Pick <math>k=k_0=1</math>:
 +
 
 +
<math>f(S_{k_0}(x_k)) = (3)^2 \delta[n-(3)] \neq (2)^2 \delta[n-(3)] = S_{k_0}(f(x_k))</math>
 +
 
 +
Since <math> \exists k_0, k \ s.t. \ S_{k_0}(f(x_k)) \neq f(S_{k_0}(x_k)) </math>  (e.g., if <math>k=k_0=1</math>), f (ie, the "system") is '''time variant'''.
  
  
 
==Part B==
 
==Part B==
**coming soon...
+
We are told to assume f is linear. We would like to find input x[n] s.t. we get output y[n] = u[n-1].
 +
 
 +
<math>u[n-1] = \delta[n-1] + \delta[n-2] + \dots = \sum_{k=1}^{\infty} \delta[n-k]</math>
 +
 
 +
Let's try the following first:
 +
 
 +
<math>f(\sum_{k=0}^{\infty} x_k) = \sum_{k=0}^{\infty} f(x_k) = \delta[n-1] + 4\delta[n-2] + \dots + (k+1)^2 \delta[n-(k+1)] + \dots = \sum_{k=0}^{\infty} (k+1)^2 \delta[n-(k+1)] </math>
 +
 
 +
(Note: The first equivalence is true because f (the system) is assumed linear.)  We're pretty close, but there's the problem with the pesty constants out in front of the delta terms, and we need to get rid of those.  Since f is assumed to be linear, we can simply multiply each term by some constant (namely, <math>(k+1)^{-2}</math>) to get rid of this:
 +
 
 +
<math>f(\sum_{k=0}^{\infty} \frac{x_k}{(k+1)^2}) = \sum_{k=0}^{\infty} f(\frac{x_k}{(k+1)^2}) = \sum_{k=0}^{\infty} \frac{1}{(k+1)^2}f(x_k)</math>    (Because the system f is linear)
 +
 
 +
<math> = \frac{\delta[n-1]}{1} + \frac{4 \delta[n-2]}{4} + \dots + \frac{(k+1)^2 \delta[n-(k+1)]}{(k+1)^2} + \dots</math>
 +
 
 +
<math>= \delta[n-1] + \delta[n-2] + \dots + \delta[n-(k+1)] + \dots =  \sum_{k=0}^{\infty} \delta[n-(k+1)] =  \sum_{k=1}^{\infty} \delta[n-k] = u[n-1]</math>
 +
 
 +
Thus, the signal that produces output y[n] = u[n-1] is the input <math>x[n] = \sum_{k=0}^{\infty} \frac{x_k[n]}{(k+1)^2} = \sum_{k=0}^{\infty} \frac{ \delta[n-k]}{(k+1)^2}</math>

Latest revision as of 11:29, 11 September 2008

Part A

We are given the following: $ X_k[n]=\delta[n-k] \rightarrow \text{ system } \rightarrow Y_k[n]=(k+1)^2 \delta[n-(k+1)] \ (k \in \mathbb{Z}, k \geq 0) $

Translate this into math: (See this for symbology.)

We are given some signal $ x_k=\delta[n-k] $ and a system $ f(x_k) = f(\delta[n-k])) = (k+1)^2 \delta[n-(k+1)] $. To show f is time-invariant, we must prove the following statement:

$ S_{k_0}(f(x_k)) = f(S_{k_0}(x_k)) \forall k_0 \text{ and }\forall k \in\mathbb{N}\cup{0} $

$ f(S_{k_0}(x_k)) = f(S_{k_0}(\delta[n-k])) = f(\delta[n-(k+k_0)]) = (k+k_0+1)^2 \delta[n-(k+k_0+1)] $

$ S_{k_0}(f(x_k)) = S_{k_0}(f(\delta[n-k])) = S_{k_0}((k+1)^2 \delta[n-(k+1)]) = (k+1)^2 \delta[n-(k+k_0+1)] $

Pick $ k=k_0=1 $:

$ f(S_{k_0}(x_k)) = (3)^2 \delta[n-(3)] \neq (2)^2 \delta[n-(3)] = S_{k_0}(f(x_k)) $

Since $ \exists k_0, k \ s.t. \ S_{k_0}(f(x_k)) \neq f(S_{k_0}(x_k)) $ (e.g., if $ k=k_0=1 $), f (ie, the "system") is time variant.


Part B

We are told to assume f is linear. We would like to find input x[n] s.t. we get output y[n] = u[n-1].

$ u[n-1] = \delta[n-1] + \delta[n-2] + \dots = \sum_{k=1}^{\infty} \delta[n-k] $

Let's try the following first:

$ f(\sum_{k=0}^{\infty} x_k) = \sum_{k=0}^{\infty} f(x_k) = \delta[n-1] + 4\delta[n-2] + \dots + (k+1)^2 \delta[n-(k+1)] + \dots = \sum_{k=0}^{\infty} (k+1)^2 \delta[n-(k+1)] $

(Note: The first equivalence is true because f (the system) is assumed linear.) We're pretty close, but there's the problem with the pesty constants out in front of the delta terms, and we need to get rid of those. Since f is assumed to be linear, we can simply multiply each term by some constant (namely, $ (k+1)^{-2} $) to get rid of this:

$ f(\sum_{k=0}^{\infty} \frac{x_k}{(k+1)^2}) = \sum_{k=0}^{\infty} f(\frac{x_k}{(k+1)^2}) = \sum_{k=0}^{\infty} \frac{1}{(k+1)^2}f(x_k) $ (Because the system f is linear)

$ = \frac{\delta[n-1]}{1} + \frac{4 \delta[n-2]}{4} + \dots + \frac{(k+1)^2 \delta[n-(k+1)]}{(k+1)^2} + \dots $

$ = \delta[n-1] + \delta[n-2] + \dots + \delta[n-(k+1)] + \dots = \sum_{k=0}^{\infty} \delta[n-(k+1)] = \sum_{k=1}^{\infty} \delta[n-k] = u[n-1] $

Thus, the signal that produces output y[n] = u[n-1] is the input $ x[n] = \sum_{k=0}^{\infty} \frac{x_k[n]}{(k+1)^2} = \sum_{k=0}^{\infty} \frac{ \delta[n-k]}{(k+1)^2} $

Alumni Liaison

Basic linear algebra uncovers and clarifies very important geometry and algebra.

Dr. Paul Garrett